Critique du rythme : Anthropologie historique du langage - Meschonnic, Henri (Lagrasse Verdier, 1982)
Rhythm is the utopia of meaning. It is on the basis of the absence of rhythm in meaning and of meaning in rhythm, in our culture of language, that this book attempts to found a new theory of rhythm. What is at stake goes far beyond the history and theory of literary practice, where poetry remains the most vulnerable and revealing place for what a society makes of the individual. Insofar as this issue engages the whole of language, it engages the whole of the subject, all subjects, and that is why, through the problems traversed, such as the relationship between language and music, voice and diction or typography, through the strategies analysed, from metrics to psychoanalysis, linguistics to philosophy, right down to its technical aspects, the theory of rhythm is, in the broadest sense, political. It is a critical journey through the human sciences. Crossing their gaps, this book sketches out a new way of working on their relationships. In a constant back-and-forth between the analysis of texts and the search for concepts, it compares the fields of French, English, German, Russian, Spanish, Hebrew and Arabic. It is aimed at anyone interested in language. It goes beyond erudition to show the adventure. (Translated with DeepL.com)
Keywords: Rhythm; Linguistics; Philosophy